Can self-determination motive predict creative thinking among university students? - Algharaibeh, Salem Ali Salem; Ghbari, Thaer A.; Almomani, Rana Thani (Creativity Studies, 2025)
Creative thinking is considered as one of the important mental processes in success in life in general and in the university, as it plays an important role in the development and progress of societies in all fields, especially considering the scientific and technological revolution and the great acceleration in all areas of life. The progress and development of societies can be measured by the level of their individuals’ possession of thinking skills in general and creative thinking. There are many variables that can play an important role in creative thinking, one of these factors is the motivation of self-determination. The current study aimed to reveal the predictive ability of self-determination of creative thinking and whether there are statistically significant differences in them due to gender and college. The sample of the study consisted of 367 university students in Jordan who were selected by the cluster random method. To achieve the objectives of the study, two measures of self-determination motivation and creative thinking scale were used. The results showed that the level of creative thinking among the study sample was low in all dimensions of the scale, and there were no statistically significant differences in creative thinking attributed to gender, except for flexibility in which males outperformed females in a statistically significant way, and there were no differences due to the college variable. The results also indicated that self-determination predicts creative thinking among university students.